Pothole Detection Using Iot Devices - K.M. , Umamaheswari; R. , Pranavchandran; R. , Aneerudh (International Journal of Psychosocial Rehabilitation, 2020)
The project deals with constructing a pothole detector for vehicles, particularly 4-wheelers. Here the purpose of this project lies in detecting potholes on roads and maintaining a database of the coordinates of such places. These coordinates are then shared with the municipal corporation to take further actions. All these are achieved through a collection of sensors and actuators. The detector is fit under the vehicle. When there is a pothole approaching, the detector scans using its infrared and ultrasonic sensor. Also, further confirmation can be given by the vibrational sensor when the vehicle falls in the pothole. When there is a confirmation of a pothole, the GPS is accessed, and the coordinates of that place are noted and stored in a small database, using it for further communication with the concerned authorities.